2013
DOI: 10.1016/j.rpor.2013.04.026
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between clinical findings and magnetic resonance imaging for the assessment of local response after standard treatment in cervical cancer

Abstract: Physical exam remains an essential tool to evaluate the local response to RT/ChT for cervical cancer. The optimal clinical radiological correlation found at 6 months after treatment suggests that the combination of gynecological examination and MRI are probably adequate in patient monitoring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…14,15 What is more, literature provides a vast range of evidence that, in comparison with Fig. 1 -The linear regression analysis for (a) the tumor width and (b) thickness between the gynecological and MRI examination at the first examination (at diagnosis).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14,15 What is more, literature provides a vast range of evidence that, in comparison with Fig. 1 -The linear regression analysis for (a) the tumor width and (b) thickness between the gynecological and MRI examination at the first examination (at diagnosis).…”
Section: Discussionmentioning
confidence: 99%
“…A good correlation (60%) between gynecological exam and MRI was also obtained by Valduvienci in his assessment of the local response after treatment. 39 Last but not least, at the second examination we considered the tumor dimension to be zero if the macroscopic tumor was not visualized at the cervical level.…”
Section: Fig 2 -The Linear Regression Analysis For the (A) Tumor Widmentioning
confidence: 99%
“…Classically, tumor response is assessed by clinical examination, pelvic MRI and [ 18 F]FDG-PET/CT 3 months after completion of treatment. Valduvieco et al reported a 60% correlation between MRI and clinical findings at 3 months with a further increase of up to 80% at 6 months [108]. Vincens et al [109] reported a false-positive rate of 50% between MRI and pathological findings.…”
Section: Adjuvant Hysterectomy (Ht)mentioning
confidence: 98%
“…MRI is useful for early detection of recurrent cervical cancer following surgery or radiation therapy [58,[61][62][63][64] (Figure 5). CT and MRI are used frequently as follow-up imaging modalities in such patients.…”
Section: Early Detection Of Recurrent Cancermentioning
confidence: 99%
“…CT and MRI are used frequently as follow-up imaging modalities in such patients. CT has difficulty identifying small recurrent cancer in the vaginal stump or uterine cervix due to poor soft tissue contrast [61][62][63]. In cases where a recurrent tumor projects into the pelvic cavity or is growing into the uterine body, visual assessment rarely allows early detection on CT. For these reasons, regular follow-up with MRI is necessary to observe signal changes at the vaginal stump or uterine cervix [62].…”
Section: Early Detection Of Recurrent Cancermentioning
confidence: 99%